The resonant population of asteroids in librating states of the υ6 linear secular resonance - Huaman, M. [UNESP]; Roig, F.; Carruba, V. [UNESP]; Domingos, R. C. [UNESP]; Aljbaae, S. [UNESP] (Oxford University Press (OUP), 2018)
We discuss the asteroid population evolving close by or into the υ6 secular resonance in the main asteroid belt. Using the analytical method of Yoshikawa, we estimate the actual domain of the υ6 resonance, which currently contains 4 137 asteroids identified from the AstDys catalogue.We perform numerical integrations of the obits of these asteroids, considering the gravitational perturbation of all the planets, and identify those showing pure libration states. For the first time, seven asteroids are found to librate in aligned states, all located at the central main belt. We analyse the stability of this new population by extending our numerical integrations both into the past and into the future, to find that all of them are stable, but only four of them display long-term aligned librations. We also identified the asteroid families located close to and within the domain of the υ6 secular resonance, with a particular focus on the Svea family, which has 54 per cent of its members librating in anti-aligned states. This is the third family identified to be largely affected by the υ6 resonance, together with the families of Tina and Euphrosyne.
Keywords: Asteroids: general; Celestial mechanics; Minor planets